EVASÃO NO ENSINO SUPERIOR PRIVADO: Um estudo de caso de uma IES de Santa Maria/RS - Santos , Walter Chalegre dos (2021)
The project has as its theme the Dropout in Higher Education and proposes a survey to identify the main reasons that lead students entering private higher education and to drop out in their first year. From this initial context, the research problem that seeks to answer in this study is: What are the reasons that lead freshmen students to evade the presence of higher education in a private institution in Santa Maria, RS? To analyze the reasons that lead freshman students to drop out of the face-to-face Higher Education of a private institution in Santa Maria, RS. The specific objectives are: to identify the main reasons that hinder the permanence of the freshman student in Higher Education; compare survey data with local, state, and national dropout rates in private Higher Education; reflect on the new possibilities of actions to reduce the dropout of incoming students. The research will have bibliographic and documental analysis procedures and the instrument to be used for the collection of research data will be the questionnaire. The data collection period will be for newcomers from 2015 to the Law courses and 2016 to the Physical Education course. This work is academically justified, as access to and permanence in Higher Education are fundamental themes for social development and contributes to the studies of the Line of Research in Teaching and academic practices, which is dedicated to the educational context, through the bet on contextualized and innovative education. It is hoped that this project will contribute to the reflections that aim to understand evasion in private higher education.